Analisis Perceraian Akibat Pernikahan Dini - Mazidatul Khoiriyah Al Basyiroh; Abdullah Afif (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Probolinggo Regency is an area where the people are a mix of Javanese and Madurese but the majority are Madurese so early marriage has become commonplace. The Probolinggo community is an example of a community that is still surrounded by the problem of increasing divorce caused by early marriage. This research aims to analyze the causes of divorce due to early marriage. The type of research used is qualitative descriptive research. Data collection techniques in this research are observation, interviews and documentation. The data analysis techniques used are data classification, data reduction, data description and conclusions. Meanwhile, testing the validity of the data used is triangulation. Factors that cause divorce due to early marriage are arranged marriages, accidents (marriage by accident), lack of income, spouse disappearing without news, likes to speak rudely or even be rude to the spouse, one of the spouses is selfish, one of the spouses often leaves the house without permission , often unclear jealousy, one partner is often angry without clarity and their existence is not appreciated.